STATE CAPTURE: CASE OF SOUTH AFRICA - Bester, Deretha; Dobovšek, Bojan (NBP. Nauka, bezbednosti, policija, 2021)
“Grand corruption” and “state capture” are two intertwined concepts of corruption that have become systemic and institutionalized in many transitional countries around the world. “State capture” can simply be defined as “the payment of bribes at high levels of government in order to extract or plunder significant amounts of money from the state”. The following paper will argue that when state capture occurs in transitional countries, it runs the risk of becoming socially embedded and institutionalized, which in turn makes it difficult to maintain the principles of democracy and threatens the overall stability of a country in transition. South Africa makes for a useful case study because it clearly represents how corruption in the form of state capture has infiltrated the political landscape of a country in transition, thereby rendering all state institutions redundant and threatening the principles of democracy. The paper will research what the dangers of state capture means for the countries in transition with the aim of proposing recommendations of minimizing state capture in order to reduce the negative consequences for security, peace and democracy. One corruption scandal that occurred in South Africa will be described which became known as “state capture”. The paper was prepared based on the analysis of documents, academic and media articles that focus on state capture and the corruption in transitional countries. The paper will conclude that governmental corruption has become socially embedded in the “logics” of negotiation and interaction, thereby indicating that it has become institutionalized and culturally embedded within South Africa.